Histological and Histochemical Studies of Sebaceous Glands of Goats (Capra hircus) - Mainde, U.P. (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on 220 skin samples from 20 goats divided into two groups.Â Histologically, the structure of sebaceous glands was simple branched alveolar type. The depth of sebaceousÂ glands was maximum in dorsal neck region and minimum in medial thigh region. The secretary part of glands was round to oval, rectangular or triangular in shape with short duct in hair canal. The glandular portion of glandÂ composed of several layers of cells.